ICT Sebagai Alat Bantu Pembelajaran di SMPIT Hidayatul Mubtadi-IEN - Syafiatun Nabila; Ahmad Farihin (Al-Qiyadi Jurnal Manajmen Pendidikan Islam, 2023)
This article aims to explain ICT as a learning aid at SMPIT Hidayatul Mubtadiien. Using a descriptive qualitative approach to collect data in the field to explain the phenomena that occur. Data collection is done through observation, interviews, and documentation. Three stages are performed in this analysis model: data reduction, data presentation, and conclusion drawing. The results of this study explain that the use of ICT as a learning aid at SMPIT Hidayatul Mubtadi-ien is very helpful in the teaching and learning process, because using ICT media makes it easier for teachers to find subers or learning methods to spill their material according to their lesson schedule. While our school has principles in the use of this technology in order to improve the ability of children in electronic media to access how widespread education in Indonesia is and knowledge that we do not yet know which we limit lest the religious values applied here are lost. The obstacle in supporting the use of ICT in the form of chromebooks in this school is that the Wi-Fi is not strong enough so obstacles like this hinder the learning process.